Studi Perbandingan Efektivitas Dan Efisiensi Sevima Web Dan Aplikasi Sevima Dalam Mendukung Aktivitas Akademik Mahasiswa - Maharani Maharani; Nurani Nurani; Nurkhalik Wahdanial Asbara (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2025)
This study aims to analyze: (1) The influence of the effectiveness and efficiency of Sevima Web and the Sevima Application on students' academic activities; (2) The simultaneous influence of the effectiveness and efficiency of Sevima Web and the Sevima Application on students' academic activities; (3) The most dominant variable between Sevima Web and the Sevima Application influencing students' academic activities. This research employs a quantitative method, with a sample of 87 respondents who are students of the Institut Teknologi dan Bisnis Nobel Indonesia. Data was collected using a Likert-scale questionnaire and analyzed using multiple linear regression analysis. The results indicate that: (1) The effectiveness and efficiency of the Sevima Application have a partial effect on students' academic activities, while the effectiveness and efficiency of Sevima Web do not have a partial effect; (2) The effectiveness and efficiency of Sevima Web and the Sevima Application have a positive simultaneous effect on students' academic activities; (3) The effectiveness and efficiency variable of the Sevima Application is the most dominant, having a positive and significant influence on students' academic activities.